(untitled) (Spandan, 2023)
This review article explores the integration of Indigenous knowledge systems (IKS) into chemistry education in higher education, focusing on how these perspectives can enhance learning. Traditional chemistry education has been dominated by Western models, which frequently exclude the rich, practical knowledge developed by Indigenous communities over centuries. The article argues that incorporating IKS into chemistry education fosters inclusivity and engages students, particularly in regions like Nepal, where Indigenous knowledge plays a significant cultural role. From interdisciplinary studies and case analyses, this review study theorizes the possibility of decolonizing chemistry education through a culturally responsive pedagogy, emphasizing the interconnectedness of life, land, and resources essential in IKS.